A facile one-pot synthesis of 2-o-cyanoaryl oxazole derivatives mediated by CuCN. Issue 14 (4th April 2018) - Fan, Senbao; Tong, Tao; Fang, Liting; Wu, Jingyi; Li, Erfei; Kang, Honglan; Lv, Xin; Wang, Xiaoxia
Graphical abstract: Highlights: It provides a convenient and efficient access to 2- o -cyanoaryl oxazole derivatives. Various substituents are well tolerated under these conditions. The formation of oxazole ring at the ortho -position favors the cyanation process. CuCN plays dual roles as a Lewis acid catalyst and a cyanide anion source. Abstract: A convenient, inexpensive and effective approach to the synthesis of 2- o -cyanoaryl oxazole derivatives has been developed. Generally, the copper-mediated cyclization/coupling reactions afforded corresponding 2-cyanoaryl oxazoles and oxazolines in moderate to excellent yields. The functionalized oxazole derivatives may be useful in biological chemistry and medicinal science. Our investigation indicates that the formation of the oxazole ring might favor the CC bond forming process on the ortho -position of the aryl ring. And CuCN plays dual roles as a Lewis acid catalyst and a C -nucleophile in this transformation.